Nutritional profile, bioactive compounds, and antioxidant activity of microalgal strain, Amphora sp., isolated from the Cape coastal waters, South Africa - BEEKRUM, Lamees Sharlynn; AMONSOU, Eric Oscar (Food Science and Technology, 2023)
Microalgae represent a potential source of renewable nutrition, and there is growing global interest in algae-based dietary supplements. However, the selection of suitable and indigenous microalgae species is a fundamental requirement in developing value-added bioactive compounds in the food industry. The proximate composition, fatty acids, amino acids, and mineral profile, as well as bioactive compounds and antioxidant activity of an unexplored diatom strain, Amphora sp. WCA23.2, isolated from the Cape coastal waters, South Africa, were evaluated as a potential nutraceutical. The Amphora sp. WCA23.2 biomass had 44.2% ash, 28% carbohydrates, 15% protein, and 4% lipids. The fatty acid profile revealed that the diatom accumulates a significant amount of omega-7-monounsaturated fatty acid palmitoleic acid (24.50 mg/g), while the amino acid profile demonstrated that it contained all the nine essential amino acids. The antioxidant activities of the diatom extracts showed that the methanolic extract displayed the highest DPPH radical scavenging activity (1.90±0.11 mg GAE/g dry weight (DW)) and the lowest IC50 in all the antioxidant indices evaluated. These results suggest that Amphora sp. WCA23.2 biomass and its extracts can be utilized as a potential source of ingredients and nutraceuticals in food systems for humans.